2009
DOI: 10.1017/s1366728909990071
|View full text |Cite
|
Sign up to set email alerts
|

Back to basics: Incomplete knowledge of Differential Object Marking in Spanish heritage speakers*

Abstract: The obligatory use of the preposition a with animate, specific direct objects in Spanish (Juan conoce a María "Juan knows Maria") is a well known instance of Differential Object Marking (DOM) (Torrego, 1998; Leonetti, 2004). Recent studies have documented the loss and/or incomplete acquisition of several grammatical features in Spanish heritage speakers (Silva-Corvalán, 1994; Montrul, 2002, 2004), including DOM (Montrul, 2004a). This study assesses the extent of incomplete knowledge of DOM in Spanish heritage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
127
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(141 citation statements)
references
References 41 publications
10
127
2
2
Order By: Relevance
“…Polinsky (1997Polinsky ( , 2006 discusses the erosion of the Russian genitive of negation, which is learned late in L1 acquisition and is generally quite infrequent. Similar erosion has been documented in Spanish (Montrul 2004, Montrul & Bowles 2009, 2010. Spanish does not have a genitive of negation, but it does have differential object marking (DOM) with animate, specific direct objects, as well as differential subject marking (DSM) with dative subjects of psychological predicates.…”
Section: Semanticssupporting
confidence: 82%
See 1 more Smart Citation
“…Polinsky (1997Polinsky ( , 2006 discusses the erosion of the Russian genitive of negation, which is learned late in L1 acquisition and is generally quite infrequent. Similar erosion has been documented in Spanish (Montrul 2004, Montrul & Bowles 2009, 2010. Spanish does not have a genitive of negation, but it does have differential object marking (DOM) with animate, specific direct objects, as well as differential subject marking (DSM) with dative subjects of psychological predicates.…”
Section: Semanticssupporting
confidence: 82%
“…It is probably more accurate to treat this phenomenon not as the overgeneralization of the nominative per se but as the extensive use of the unmarked case; general, unmarked case accounts for the bulk of object forms (replacing the accusative). The same change, from differential object marking with a to an unmarked object case, is observed in Heritage Spanish (Montrul 2004, Montrul & Bowles, 2009). …”
Section: Structural Vs Inherent Casesupporting
confidence: 61%
“…Montrul and Bowles (2009) tried to account for these findings proposing that they could be the result of the lack of perceptual salience of the structure in question. In many occasions, the final vowel of the verb and the preposition are reduced to one sound if the verb ends in [a], as in (4), or they are diphthongized, as in (5), which makes the preposition difficult to be recognized.…”
Section: Acquisition Of the Spanish Personal Prepositionmentioning
confidence: 99%
“…Montrul (2010a) cites various studies that suggest that heritage speakers are outperformed by native speakers in a variety of grammatical measures. Montrul (2010a) notes that heritage speakers of Spanish perform worse than their monolingual counterparts in gender marking (Montrul, Foote, & Perpiñán 2008), the subjunctive mood (Silva-Corvalán, 1994), usage of the dative preposition "a" (Montrul & Bowles, 2009), and differential object marking (Montrul, 2010b). SilvaCorvalán (1991SilvaCorvalán ( , 1994 has shown that HS suffer considerable L1 attrition, in part caused by the contact situation between their L1 and the majority language, English.…”
Section: Motivation For Study and Research Questionsmentioning
confidence: 99%